Anorexia nervosa and Wernicke-Korsakoff syndrome: a case report - Saad, Laura (BioMed Central, 2010)
INTRODUCTION: Wernicke's encephalopathy is an acute, potentially fatal, neuropsychiatric syndrome resulting from thiamine deficiency. The disorder is still greatly under-diagnosed, and failure to promptly identify and adequately treat the condition can lead to death or to the chronic form of the encephalopathy - Korsakoff's syndrome. Wernicke's encephalopathy has traditionally been associated with alcoholism but, in recent years, there has been an increase in the number of clinical settings in which the disorder is observed. CASE PRESENTATION: We report the case of a 45-year-old Caucasian woman who arrived at the emergency room presenting signs of marked malnutrition and mental confusion, ataxic gait and ophthalmoplegia. Main laboratory test findings included low serum magnesium and megaloblastic anemia. Brain magnetic resonance imaging revealed increased T2 signal in the supratentorial paraventricular region, the medial regions of the thalamus and the central and periaqueductal midbrain. The diagnosis of Wernicke's encephalopathy was made at once and immediate reposition of thiamine and magnesium was started. The patient had a long history of recurrent thoughts of being overweight, severe self-imposed diet restrictions and self-induced vomiting. She had also been drinking gin on a daily basis for the last eight years. One day after admittance the acute global confusional state resolved, but she presented severe memory deficits and confabulation. After six months of outpatient follow-up, memory deficits remained unaltered. CONCLUSION: In this case, self-imposed long-lasting nutritional deprivation is thought to be the main cause of thiamine deficiency and subsequent encephalopathy, but adjunct factors, such as magnesium depletion and chronic alcohol misuse, might have played an important role, especially in the development of Korsakoff's syndrome. The co-morbidity between eating disorders and substance abuse disorders has emerged as a significant health issue for women, and the subgroup of patients with anorexia nervosa who also misuse alcohol is probably at a particular risk of developing Wernicke-Korsakoff syndrome. The present case report highlights this relevant issue.